On the Acceleration Site of Anomalous Cosmic Rays: Voyager 2 Observations of Their Anisotropy in the Heliosheath - A. C. Cummings; J. Kóta; J. D. Richardson; J. S. Rankin; B. C. Heikkila (The Astrophysical Journal)
We present the diffusive flow anisotropy vector components for ∼0.5–35 MeV anomalous cosmic-ray (ACR) protons observed during Voyager 2 roll maneuvers for the magnetometer instrument in the inner heliosheath. The diffusive flow results are derived from the differences between the observed anisotropy components presented in A. C. Cummings et al. (2021) and the Compton–Getting anisotropies based on measurements of the solar wind speeds from the Plasma Science instrument. We find that the tangential component of the derived diffusive anisotropy vector is in reasonable agreement, both in direction and magnitude, with a numerical model of the acceleration and transport of ACRs by diffusive shock acceleration along a nonspherical solar wind termination shock (TS). The results suggest that there exists a diffusive flow of these particles from the flank or tail of the heliosphere toward the nose, and support models in which higher-energy ACRs are accelerated in the flank or tail of the TS.